Food and water security [ - Aswathanarayana, U. (London ; New York : Taylor & Francis, 2008)
The UN Millennium Summit in 2000 pledged to achieve a set of Millennium Development Goals to be achieved by 2015. They include halving by 2015 the number of undernourished people in the world, which currently stand at 850 million people. This book explores ways and means of achieving the Millennium Development Goal in respect of Food Security. With contributions from world experts.
Description based on print version record
Includes bibliographical references and indexes
Keywords: Food supply -- Developing countries; Sustainable agriculture -- Developing countries; Water-supply -- Developing countries